2017
DOI: 10.3846/btp.2017.020
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis Evaluation of Schein’s Career Orientations Inventory in Colombia

Abstract: The Career Orientation Inventory model proposed by Edgar Schein is one of the most discussed methods for identifying individuals’ career orientations. However, there are several gaps related to its implementation for developing countries using factor analysis and digital open access data. We conducted exploratory and confirmatory factor analysis for a sample of 116 employees of a contact center in Colombia to test whether there were significant differences among career anchors (CAs) and gender, educational att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In contrast, FA is a very widespread and noted technique within many other branches of science, e.g. social and psychological sciences and marketing research (Thurstone, 1947;Nawojczyk, 2002;Brown, 2006;Cortés Sánchez & Grueso Hinestroza, 2017;Chidambaram et al, 2013;Ludwikowska, 2021;Warter & Warter, 2017). The reason may be related to the lack of statistical awareness, laborious data collection, computational complexity, and problematic interpretation of abstractive factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, FA is a very widespread and noted technique within many other branches of science, e.g. social and psychological sciences and marketing research (Thurstone, 1947;Nawojczyk, 2002;Brown, 2006;Cortés Sánchez & Grueso Hinestroza, 2017;Chidambaram et al, 2013;Ludwikowska, 2021;Warter & Warter, 2017). The reason may be related to the lack of statistical awareness, laborious data collection, computational complexity, and problematic interpretation of abstractive factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, organizations and occupational groups themselves are not expected to cause individuals to maintain or abandon predetermined anchors. In addition, many studies have indicated that career orientations could differ among race (Coetzee et al, 2007;Oosthuizen et al, 2014), gender (Igbaria et al, 1991, Kniveton, 2004Coetzee et al, 2007;Coetzee & Schreuder, 2008;Coetzee & de Villiers, 2010; Cortés-Sánchez & Grueso-Hinestroza, 2017), age (Kniveton, 2004;Coetzee & Schreuder, 2008;Oosthuizen et al, 2014), educational level (Coetzee & Schreuder, 2008;Cortés-Sánchez & Grueso-Hinestroza, 2017) and marital status (Coetzee & Schreuder, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, it was found that congruence between person's career anchor and job has a positive impact on job satisfaction (Danziger & Valency, 2006;Steele, 2009;Igbaria et al, 1991), organizational commitment and can decrease turnover intensions (Igbaria et al, 1991;Hardin et al, 2001). It was also found that dominant career anchor of employees may differ in accordance with age, gender, race, marital status, educational level and occupation (Schein 1978;Coetzee et al, 2007;Coetzee & Schreuder, 2008;Steele, 2009;Cortés-Sánchez & Grueso-Hinestroza, 2017). This paper presents the results of the study conducted on the sample of secondary school teachers in order to find out which one of nine career anchors defined in the line with the Schein's conceptualization (1978), is dominant and how they differ in terms of demographic factors such as gender, age and work experience.…”
Section: Introductionmentioning
confidence: 99%